2017
DOI: 10.1248/bpb.b17-00175
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Lasting Enhancing Effect of Distigmine on Acetylcholine-Induced Contraction of Guinea Pig Detrusor Smooth Muscle Correlates with Its Anticholinesterase Activity

Abstract: Distigmine bromide (distigmine), a reversible, long-lasting cholinesterase (ChE) inhibitor, is used for the treatment of underactive bladder in Japan and has been shown to potentiate urinary bladder (UB) contractility. We studied the duration of distigmine's potentiating effects on acetylcholine (ACh)-induced UB contraction and its inhibitory effects on ChE activity, and compared that with those of other ChE inhibitors (neostigmine, pyridostigmine, and ambenonium). The duration of potentiating/inhibitory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Furthermore, the k diss values of pyridostigmine and neostigmine determined in the present study (0.51±0.05 and 0.66±0.03 h , respectively). 18) However, the value obtained for ambenonium with rhAChE (1.41±0.08 h ). Although we do not have a clear explanation for this difference at present, one plausible explanation could be the presence of Cl in the structure of ambenonium (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Furthermore, the k diss values of pyridostigmine and neostigmine determined in the present study (0.51±0.05 and 0.66±0.03 h , respectively). 18) However, the value obtained for ambenonium with rhAChE (1.41±0.08 h ). Although we do not have a clear explanation for this difference at present, one plausible explanation could be the presence of Cl in the structure of ambenonium (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, our laboratory started pharmacological studies on the effects of distigmine on urinary bladder (UB) motility and has previously reported results supporting the clinical effectiveness and usefulness of distigmine. [10][11][12][13][14][15][16][17][18] The most remarkable pharmacological characteristic of distigmine was the persistence of its effect. In particular, distigmine was found to potentiate the UB internal pressure via the micturition reflex for more than 12 h. 17) Interestingly, the long-lasting potentiating effect of distigmine on intravesical pressure persisted even after distigmine disappeared from the blood.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ito et al also reported that rat erythrocyte AChE inhibition by distigmine did not correlate with the plasma concentrations of this drug following oral administration. 22) The possibility that active metabolites of distigmine generated by hepatic metabolism contribute to these pharmacodynamic effects cannot be completely ruled out at present, although this seems unlikely because: 1) distigmine was reported to be excreted by the kidneys 24) using 14 C-labeled distigmine; 2) three chemical candidates that are predicted to be generated by decomposition of distigmine did not affect AChE activity 25) ; 3) distigmine-mediated enhancement of AChinduced contraction of guinea pig urinary bladder smooth muscle lasted for ≥12 h after washing out with distigmine-free solution 25) ; and 4) distigmine inhibited recombinant human AChE activities for >48 h after the separation of distigmine from the enzyme by centrifugation (our unpublished observation). One possible explanation for this discrepancy would thus be the retention of distigmine within urinary bladder tissues or a robust binding to AChE, which would sequester the compound at its site of action.…”
Section: )mentioning
confidence: 99%